Radical System

Algebra Level 1

a + b = 7 b + a = 11 \large \sqrt a + b = 7 \\ \large \sqrt b + a = 11

If a a and b b are real numbers that satisfy the equation above, what is the value of a a and b b respectively?

a = 9 , b = 6 a = 9, b = 6 a = 6 , b = 4 a = 6, b = 4 a = 9 , b = 4 a = 9, b = 4 a = 79 , b = 3 a = 79, b = 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

12 solutions

Michael Mendrin
Sep 10, 2014

First make the substitutions x 2 = a { x }^{ 2 }=a and y 2 = b { y}^{ 2 }=b . Then we have

x + y 2 = 7 x+y^{ 2 }=7
y + x 2 = 11 y+x^{ 2 }=11

Re-arranging both, we have

( x 3 ) = ( 2 y ) ( 2 + y ) (x-3)=(2-y)(2+y)
( y 2 ) = ( 3 x ) ( 3 + x ) (y-2)=(3-x)(3+x)

Which leads to

( y 2 ) = ( 2 y ) ( 2 + y ) ( 3 + x ) (y-2)=(2-y)(2+y)(3+x)

That is

( y 2 ) ( 1 ( 2 + y ) ( 3 + x ) ) = 0 (y-2)(1-(2+y)(3+x))=0

Being that y 2 y-2 is one of the factors, b = 4 b=4 , and from that a = 9 a=9

My approach is slightly simpler, without having to notice the "nice" factorization that is implied by the answer.

I substituted the second equation into the first, to get x + ( 11 x 2 ) 2 = 7 x + ( 11-x^2)^2 = 7 , which gives us ( x 3 ) ( x 3 + 3 x 2 13 x 38 ) = 0 (x - 3)(x^3 + 3x^2 -13x - 38 ) = 0 . Hence x = 3 x = 3 is a solution.

For the cubic equation, there are 2 negative roots (which we can ignore), and the third root is about 3.5844 3.5844 . This gives us a 12.8479 a \approx 12.8479 and b 7.4156 b \approx 7.4156 . However, this doesn't satisfy the second equation because we actually have 7.4156 + 12.8479 = 11 - \sqrt{ 7.4156 } + 12.8479 = 11 .

Calvin Lin Staff - 6 years, 9 months ago

Log in to reply

Calvin, I propose a new name for one approach to solving problems. We already have "bashing" which denotes solving problems using brute force. How about "feigned prescience" to denote solutions that clearly depend on already knowing what the answer is? I see a lot of solutions of that nature, and not just here in Brilliant (some of which I'm guilty of!).

Michael Mendrin - 6 years, 9 months ago

Log in to reply

True. Sometimes I start with "This solution is based on already knowing / guessing what the answer is ...". This happens when the solution is "by magic" and hard to find the motivation.

Often, I try and drill into the solution further, and highlight certain aspects which could explain a more intuitive approach. This isn't always possible, in part because Problem Solving often has a "Ah-ha" moment that is hard to quantify down.

Calvin Lin Staff - 6 years, 9 months ago

no thats wrong..u have substituted the value of (3-x) with (x-3)..u cant do that If (x-3) = (2-y)(2+y), then (3-x) = - (2-y)(2+y)

Sonali Tare - 6 years, 1 month ago

Log in to reply

Do you know who you're talking to?

Sal Gard - 4 years, 11 months ago

Log in to reply

He is right you know.

Abdur Rehman Zahid - 4 years, 11 months ago

Interesting approach. There could be other solutions from the second factor right? So you have to explain why it is non-zero.

Calvin Lin Staff - 6 years, 9 months ago

Or you could just check all 4 possible solutions..

Alexandru Maxim - 5 years, 7 months ago

the second to last equation needs a negative sign on the right side.

Clive Chang - 5 years, 7 months ago

Log in to reply

Get a pair of spectacles, man...

Rudrayan Kundu - 2 years, 9 months ago

Brilliant! After the x^2 =a and y^2=b substitutions, simply plot a few points for the y functions y1 = +/- (7 - x)^.5 and y2 = (11- x^2). I.e., let x =0,1,2,3... At x=3, y1=y2=2. Hence, x^2=9=a, and y^2=4=b. That's a lot easier than trying to solve, a^4 - 44 a^3 +712 a^2 - 5017*a +12996 I'm ashamed to say.

Carl Dahlstrom - 5 years, 7 months ago

How are we able to make those substitutions? (still learning)

Jess Doe - 5 years, 5 months ago

For that rearrengement, you need to know the answer. Other type arrengements wont give any simplementation.

Melih Koruyucu - 3 years, 6 months ago

how is it that you didnt change the sign (y−2)=(3−x)(3+x)

Which leads to

(y-2)=(2-y)(2+y)(3+x)(y−2)=(2−y)(2+y)(3+x)

cfgvhjbjk ccgjc - 1 year, 5 months ago

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago

what if we took x=-a or y=-b

origami origami - 1 year, 1 month ago

Respected Sir, there is a little mistake .. there sould be (y-2) instead of (2-y), after Which leads to..

Bhupendra Jangir - 6 years, 5 months ago

I am most unsatisfied. To me, trial and error is picking possible solutions, then seeing which one is correct. Even the algebraic solutions calculate 4 possible answers, then pick (through trial and error) the correct one. It appears, given the stipulation that the problem disallowed trial and error, that the correct answer to the problem is "not able to be solved."

Jeff Barrett - 6 years ago

Cool mahnn.. You nailed it.. :)

Shubham Sawant - 5 years, 9 months ago

kindly elaborate more>>>>>???

Saadat Khokhar - 5 years, 5 months ago
Akhash Raja Raam
Nov 24, 2015

Only option no. 3 has two numbers which are squares. Only perfect squares can give a whole number. Its that easy.

What if they didn't have the choices?

Alan Chen - 5 years, 5 months ago

Log in to reply

Then you need to do the workings. You need to save time in exams, so look for the reasonable and LOGICAL way, if you want to find an answer quickly!

PS : It's always the survival of the fittest in the world. It's not wrong if you have a trick up your sleeve to protect you!(I hope you understood what I am trying to say!)

Akhash Raja Raam - 5 years, 3 months ago

Log in to reply

Yeah that makes sense :)

Alan Chen - 5 years, 3 months ago

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Harsha Urs
Dec 24, 2015

No need of much calculations just cheak with options. Only option 3 is matching

What if they didn't have the choices?

Alan Chen - 5 years, 5 months ago

Log in to reply

Actually, even without choices, guessing and enumeration still is the fastest way to solve this. We establish that a and b should be perfect squares since both sums are whole numbers. Looking at the first equation, we can immediately see, by listing all possible addends of 7 (7 + 0, 6 + 1, 5+ 2,...), that only 1 and 4 are perfect squares; hence unknown a must be either of those two. Suppose a is 1, we have to add 6 to it to arrive at 7, which contradicts our non-negotiable observation that both a and b must be perfect squares. Therefore a must be 4. 4 + 3 = 7 and hence b = 9.

Vin Zaid - 3 years, 3 months ago

Log in to reply

a is 9 and b is 4 not a is 4 if a is 4 b will be five bec 2+5 =10

Oximas omar - 2 years, 7 months ago

Spelling of check is incorrect

Sumukh Bansal - 3 years, 7 months ago

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Oon Han
Nov 11, 2017

Firstly, isolate b b in a + b \sqrt { a } +b b = 7 a b=7-\sqrt { a } Then subsitute it into the equation b + a = 11 \sqrt { b } +a=11 7 a + a = 11 \sqrt { 7-\sqrt { a } } +a=11 Its a square root nested in a square root! First, subtract a a 7 a = 11 a \sqrt { 7-\sqrt { a } } =11-a Then square both sides. 7 a = a 2 22 a + 121 7-\sqrt { a } ={ a }^{ 2 }-22a+121 One square root eliminated. Subtract 7 from both sides, a = a 2 22 a + 114 -\sqrt { a } ={ a }^{ 2 }-22a+114 Square both sides again! a = a 4 44 a 3 + 712 a 2 5016 a + 12996 a={ a }^{ 4 }-44{ a }^{ 3 }+712{ a }^{ 2 }-5016a+12996 Now, SOLVE THE EQUATION a = a 4 44 a 3 + 712 a 2 5016 a + 12996 a={ a }^{ 4 }-44{ a }^{ 3 }+712{ a }^{ 2 }-5016a+12996 Its tricky, and it has 4 solutions (by the a 4 { a }^{ 4 } as you can see), so I recommend using a graphing calculator and find the solutions. They are 9, 7.86869..., 12,84813..., and 14.28319... Verifying the solutions, only 9 is true. Thus, we got a = 9 a=9 Now, find b b 9 + b = 7 \sqrt { 9 } +b=7 b = 4 b=4

So, the solution set is { a = 9 , b = 4 } \{ a=9,\quad b=4\}

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Mathoholic Oja
Mar 25, 2020

Venkatachalam J
Apr 20, 2016

Backtracking from the given choice is the quickest way to find the solution, If problem did't have choice of solution we need to go with substitution method. Also there is one more hint in the problem 'a' and 'b' mostly be a perfect square.

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Haoran Zhang
May 30, 2017

a and b should be integer after extraction of a root.

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Iris Fan
Dec 27, 2016

A= 9=3+4=7

B= 4=2+9=11

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Sot Mathematician
Jun 18, 2016

It's easy to confirm via substitution in the first equation !

I have added a better solution below please check it out

Mathoholic Oja - 1 year, 2 months ago
Vino Vishwa
Dec 4, 2015

9 square is 3 and 4 square is 2 Then A value is 9 B value is 4

What if they didn't have the choices?

Alan Chen - 5 years, 5 months ago

binomial theorm 71\8

mohamed eshibae - 4 years, 10 months ago

Log in to reply

Cool thing @K T

Am Kemplin - 3 weeks, 2 days ago
K T
Mar 24, 2019

Let α = a \alpha=\sqrt{a} and β = b \beta=\sqrt{b} . We get α + β 2 = 7 \alpha+\beta^2=7 and α 2 + β = 11 \alpha^2+\beta=11 . It is clear that for real roots α [ 0 , 11 ] \alpha \in [0,\sqrt{11}] and β [ 0 , 7 ] \beta \in [0,\sqrt{7}] .

By substituting α = 7 β 2 \alpha=7-\beta^2 into α 2 + β = 11 \alpha^2+\beta=11 we get the polynomial β 4 14 β 2 + β + 38 = 0 \beta^4-14\beta^2+\beta+38=0 Hoping for rational solutions, we use the rational root theorem . This implies that any rational root β \beta has to be an integer divisor of 38, of which only 1 and 2 are in the allowed range. Checking for β = 2 \beta=2 , we see it is a solution indeed, because 16 56 + 2 + 38 = 0 16-56+2+38=0 . Now b = 4 b=4 and a = 9 a=9 follow directly.

I square that a = 9. But. There is a way to make (x + 1). and if we add 4. we will have a continuing process.

Am Kemplin - 3 weeks, 2 days ago
Khushi Jain
Nov 1, 2016

hello, we can solve this equation just by assuming... sq. root of 'a'+'b'=7, 'a'+sq. root of 'b'=11 these equations apply that a and b both are squares of a particular no. so, lets assume a=9 and b=4(as both are squares of a particular no.) so lets see if they satisfy the equation or not.. sq. root of 9=3 and sq. root of 4=2...., 3+4=7 9+2=11 here both of the equations are been satisfied.. Therefore, a=9 and b=4

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...